Morphometric subpopulations study of white-tailed deer (Odocoileus virginianus peruvianus) epididymal spermatozoa - Cucho, Hernán (2022)
Introduction. The study of the sperm morphometry of the white-tailed deer (Odocoileus virginianus peruvianus) allows to characterize the sperm cells of this species for conservation purposes. Objective. To determine the sperm subpopulations according to the morphometry of the epididymal spermatozoa of the white-tailed deer, using a CASA-Morph system. Materials and methods. The study was carried out in the second semester 2016, at the Universidad Nacional San Antonio Abad del Cusco, Peru. In semen samples obtained from the caudal end of the epididymis of two deer (two and four teeth), it was determined based on the CASA-Morph system, Integrated Semen Analysis System (ISAS®v1): the length, width, area, perimeter, ellipticity, elongation, regularity, and roughness of the sperm head were determined, also, the width, area, distance, and midpiece insertion angle of the sperm. Principal components analysis (PCA) was performed and the non-hierarchical k-means model was applied to determine the optimal number of clusters. Results. The morphometric variables were distributed in five PCAs: ellipticity, size, circularity, midpiece insertion angle, which explained 81.24 % of the total variance. The Cluster analysis determined four subpopulations (SP), SP1 grouped large, elongated cells with high elongation and ellipticity (21.76 %), SP2 composed of small and thin spermatozoa both in the head and in the midpiece (37.7 %). The SP3 was related to the presence of elongated cells with high values of midpiece width, ellipticity, and elongation (17.7 %), and SP4 grouped spermatozoa with intermediate size of the head and the midpiece (22.84 %). Conclusion. The determination of four sperm subpopulations in white-tailed deer semen can be the basis of assisted reproduction programs for this species.